Pharyngeal airway dimensions and adipose distribution in the minipig - Doris H. Rosero Salazar; Riana Grewal; Anuj Vimawala; Daniel F. Leotta; Swati R. Levendovszky; Zi-Jun Liu (Journal of Oral Biology and Craniofacial Research)
Objective: To evaluate the pharyngeal airway dimensions and regional pharyngeal adipose distribution in the young adult minipig model. Materials and methods: Eight 7-8-months-old Yucatan minipigs, half male and female, were sedated and placed prone to scan the pharyngeal region. Magnetic resonance imaging (MRI) was performed using dynamic turbo-field echo (TFE)-sequence with respiratory gating and adipose-weighted sequence. Respiratory airflow velocity, pressure, and volume were also recorded. The sizes of velopharyngeal and oropharyngeal airway, and retroglossal areas were measured coronally during inspiration and expiration. The airway volumes from the nasal cavity to the retroglossal space were segmented, reconstructed, and evaluated in sagittal views. The adipose distribution in the tongue base, soft palate, pharyngeal wall, tongue body, and masseter muscle (reference) were segmented and measured in sagittal and coronal planes. Results: The velopharyngeal and oropharyngeal areas were larger in inspiration than in expiration. These areas were also larger than that in the retroglossal space (p < 0.05). The nasal cavity showed a larger volume than that of the pharyngeal regions (p < 0.05). The adipose distribution was larger in the posterior region of the tongue base and anterior soft palate, both larger than the masseter muscle (p < 0.05). Conclusion: The larger oropharyngeal dimensions and increased adipose distribution in the tongue base contribute to the functional morphology of the pharyngeal airway in the healthy minipig. These data provide the baseline for further analysis in enlarged and reduced tongue base minipig models.